Reply to: Looking Before We Leap: Building the Evidence for Social Prescribing for Lonely Older Adults. Issue 2 (16th December 2019) - Mulligan, Kate; Bhatti, Sara; Rayner, Jennifer; Hsiung, Sonia
Abstract : This is a response to the article by Savage et al .